1993
DOI: 10.1073/pnas.90.24.11748
|View full text |Cite
|
Sign up to set email alerts
|

Human cytochrome P450 3A4: enzymatic properties of a purified recombinant fusion protein containing NADPH-P450 reductase.

Abstract: Human cytochrome P450 3A4is recognized as the catalyst for the oxygen-dependent metaboism of a diverse group of medicafly important chemicals, inWuding the immunosuppressive agent cyclosporin; macrolide antibiotics, such as erythromycin; drugs such as benzphetamine, nifedipine, and cocaine; and steroids, such as cortisol and testosterone to name but a few. We have engineered the cDNA for human cytochrome P450 3A4 by linkage to the cDNA for the rat or human flavoprotein, NADPH-P450 reductase (NADPH:ferrihemopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 30 publications
4
55
2
1
Order By: Relevance
“…The first published was a fusion of rat CYP1A1 and yeast RED 22 and was expressed in yeast. Since then several groups have constructed fusion proteins including human CYP3A4 fused to rat RED 21 and expressed them in bacteria 24,25,41 for functional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first published was a fusion of rat CYP1A1 and yeast RED 22 and was expressed in yeast. Since then several groups have constructed fusion proteins including human CYP3A4 fused to rat RED 21 and expressed them in bacteria 24,25,41 for functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression can be achieved either as two separate proteins 19 or with the construction of a fusion protein linking CYP2B6 and RED in one gene. Previous efforts to fuse the two genes have resulted in active proteins; [21][22][23][24][25] however, fusion proteins have never been expressed in mammalian cells and RED has never been used in association with CYP2B6. Finally, the notion of fusing two human proteins should not produce a host immune response.…”
mentioning
confidence: 99%
“…Anionic lipids, particularly PtdSer, favour the formation of the ultimate mutagen DE2 to the detriment of that of the far less carcinogenic DE1. It has been reported that lipids affect several catalytic activities of CYP3A4 [40,41]. Thus, it would be interesting to know whether other enzymatic activities of human CYP1A1 also depend on the membrane structure and/or lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Rates were adjusted by subtracting the very low rate of NAD(P)H consumption by the flavoproteins in the absence of AhpC. Kinetic data were fit to the Michaelis-Menten equation (39)(40)(41) and the ferredoxin/ ferredoxin-NADP + reductase (Fd/FNR) fusion protein (42). In each of these cases, design of the fusion proteins was guided by naturally occurring fusions of related proteins.…”
Section: Nad(p)h-dependent Dtnb and Ahpc-linked Peroxide Reductase Acmentioning
confidence: 99%